EFEKTIVITAS KOMBINASI TARIK NAFAS DALAM DAN AFIRMASI POSITIF MENGURANGI DEPRESI PADA PERAWAT DI PUSKESMAS BANTUL YOGYAKARTA - Lovadira , Layla; Siti Fatimah, Fatma; Yugistyowati, Anafrin; Jaka Sarwadhamana, Raden (Journal of Hospital Administration and Management (JHAM), 2025)
​​Background: Depression is the most common mental health problem experienced by nurses, especially in stressful environments. It can affect performance, reduce effectiveness, and decrease work productivity. One effective method to reduce depression is deep breathing techniques, which help enhance comfort and increase the body’s resilience. Additionally, positive affirmations short, simple statements spoken aloud and repeated slowly also help build confidence and combat depression. Objective: To determine the effectiveness of combining deep breathing techniques and positive affirmations in reducing depression among nurses at Bantul Public Health Center, Yogyakarta. Method: This study used a quantitative approach with a pre-experimental design employing a one-group pretest-posttest design. The sampling technique was non-probability sampling, specifically purposive sampling. The sample consisted of 17 respondents. Data collection was conducted using pre-test and post-test questionnaires. The DASS-42 instrument was used to measure depression levels. Data analysis was performed using the Wilcoxon signed-rank test to compare depression scores before and after the intervention within the same respondents. Results: Among the 17 respondents, 15 showed a decrease in depression scores, 1 showed an increase, and 1 showed no change. The average depression score significantly decreased from 3.29 to 0.41 following the deep breathing and positive affirmation intervention, with a Wilcoxon test significance value of 0.002 (p < 0.05). Conclusion: This study demonstrated a significant reduction in depression scores following the intervention combining deep breathing and positive affirmations, indicating that the intervention is effective in reducing depression among nurses at Bantul Public Health Center. Therefore, it is recommended to implement this intervention routinely as an effort to improve the mental health of healthcare workers.